Sei sulla pagina 1di 4

# Exercise 1.

4 (Solutions)

MathCity.org

## Available online @ http://www.mathcity.org, Version: 1.0.0

Question # 1:
f ( x ) = 2x2 + x 5
(i )

c =1

2

x 1

x 1

## lim+ f ( x ) = lim+ ( 2 x 2 + x 5 ) = 2 (1) + 1 5 = 2 + 1 5 = 2

2

x 1

( ii )

x 1

lim f ( x ) = lim+ f ( x ) = 2

x 11

x 1

f ( x) =

x 9
x 3
2

lim f ( x ) = 2
x 1

C = 3

( x 2 9) ( 3)2 9 9 9 0
x 2 9 xlim
3
lim f ( x ) = lim
=
=
=
=
=0
x 3
x 3 x 3
lim ( x 3)
3 3
6
6
x 3

Now

( iii )

x 2 9 ) ( 3 ) 2 9 9 9 0
(
x 2 9 xlim
+
lim f ( x ) = lim+
= 3
=
=
=
=0
x 3+
x 3 x 3
lim+ ( x 3)
3 3
6
6
lim f ( x ) = lim+ f ( x ) = 0

x 3

x 3

x 3

f ( x) = x 5

lim f ( x ) = 0

x 3

C =5

lim f ( x ) = lim x 5

x 5

x 5 = ( x 5)

x 5

( x 5)

+ ( x 5)
+

= lim ( x 5 ) = lim ( x 5 ) = ( 5 5 ) = 0
x 5
x 5

## lim f ( x ) = lim+ x 5 = lim+ ( x 5 ) = 5 5 = 0

x 5+

x 5

x 5

lim f ( x ) = lim+ f ( x ) = 0

x 5

x 5

lim f ( x ) = 0
x 5

Question # 2:
Discuss the continuity of

f ( x ) at x = c

if
2 x + 5

f ( x ) = 4 x + 1
if
(i )

## We haveto discuss the continuity of

(a)
(b )

f ( 2 ) = 2 ( 2) + 5 = 4 + 5 = 9

x2
x>2
c=2
f ( x)

lim f ( x ) = ?
x2

at x = 2
.................... (1)

f ( x) = 2x + 5

f ( x) = 4x +1
2

lim f ( x ) = lim ( 2 x + 5 ) = 2 ( 2 ) + 5 = 4 + 5 = 9

x 2

and

x2

lim f ( x ) = lim ( 4 x + 1) = 4 ( 2 ) + 1 = 8 + 1 = 9

x 2 +

x2

lim f ( x ) = 9 ............... ( 2 )
x2

FSc-II/Ex 1.4-2

(c)

from

(1) and ( 2 )
lim f ( x ) = f ( 2 )
x2

f ( x ) is continous at x = 2
( ii )

3 x 1

f ( x ) = 4
2 x

if

c=2

we get

if x < 1
x =1 c = 2
x >1
f (c) = f ( 2)

( ii )

Correction
3 x 1

f ( x ) = 4
2 x

c =1

if x < 1
if x = 1
if x > 1

( correction )

f (1) = 4
1

(a)
(b )

f ( x ) = 3x 1

f (1) = 4

f ( x) = 2x

( given )

lim f ( x ) = ?

x 1

x 1

x 1

and

## lim+ f ( x ) = lim ( 2 x ) = 2 (1) = 2

lim f ( x ) = lim+ f ( x ) = 2

lim f ( x ) = 2 ............................. ( 2 )

(c)

(1) and ( 2 )
lim f ( x ) f (1)
x 1
f ( x ) is discontinous at

x 1

x 1

x 1

x 1

x 1

From

( iii )

(a)

f (1)

we get
x =1

3 x 1

f ( x) =
2 x

if x < 1
c =1
if x > 1

is not defined

f ( x ) is discontinous at x = 1

Question # 3:
Given that
if
3 x
2
f ( x ) = x 1 if
3
if

f ( x ) = 3x

(i )
(a)

x 2
2 < x < 2
x2
f ( x) = x 1
2

+
f ( x) = 3

We check continuity at x = 2
f ( 2) = 3

................................ (1)

( given )

## Available online at http://www.MathCity.org

FSc-II/Ex 1.4-3

(b )

lim f ( x ) = ?
x2

lim f ( x ) = lim ( x 2 1) = ( 2 ) 1 = 4 1 = 3
2

x 2

x2

x 2 +

x2

lim f ( x ) = lim ( 3) = 3
lim f ( x ) = lim+ f ( x ) = 3

x 2

x2

lim f ( x ) = 3 ....................... ( 2 )

(c)

## From (1) and ( 2 ) ,

x2

we get

lim f ( x ) = f ( 2 )
x2

f ( x ) is continuous at

( ii )
(a)
(b )

x=2

x = 2

At

f ( 2 ) = 3 ( 2 ) = 6 ............................ (1)

lim f ( x ) = ?

x 2

lim f ( x ) = lim ( 3 x ) = 3 ( 2 ) = 6

x 2

x 2

lim f ( x ) = lim ( x 2 1) = ( 2 ) 1 = 4 1 = 3
2

and

x 2+

x 2

x 2

x 2

lim f ( x ) lim+ f ( x )

lim f ( x )
x 2

f ( x ) is discontinuous at
Question # 4:
Given that
x + 2
f ( x) =
c + 2
c=?

x = 2

x 1
x > 1

f ( x) = x + 2

lim f ( x )

## does not exist

+
f ( x) = c + 2

exists

x 1

lim f ( x ) = lim+ f ( x )

x 1

x 1

lim ( x + 2 ) = lim ( c + 2 )

x 1

x 1

1 + 2 = c + 2
1 = c+2
c = 1 2

c = 1

Question # 5:
(i )
if
mx

f ( x ) = n
if
2 x + 9 if

f ( 3) = n

here
Q

x<3
x=3
x>3

( given )

f ( x ) is continuous at

x =3

lim f ( x ) = lim+ f ( x ) = f ( 3)

x 3

x 3

lim ( mx ) = lim ( 2 x + 9 ) = n
x 3

x 3

## Available online at http://www.MathCity.org

FSc-II/Ex 1.4-4

( m )( 3) = 2 ( 3) + 9 = n

3m = 6 + 9 = n
3m = 3 = n
3m = 3
,
m =1
,
if
mx
f ( x) = 2
if
x

( ii )

n=3
n=3
x<4
x4

f ( 4 ) = ( 4 ) = 16
2

here

f ( x ) is continuous at

x=4

lim f ( x ) = lim+ f ( x ) = f ( 4 )

x 4

x4

lim ( mx ) = lim ( x 2 ) = 16

4m = ( 4 ) = 16

4m = 16 = 16
m=4

x4

x4

4m = 16

Question # 6:
Given that
2x + 5 x + 7

f ( x) =
x2

K =?
here f ( 2 ) = K
given
Q
Q
lim
x2

x2

2x + 5 x + 7
=K
x2
lim
x2

2x + 5

( x 2) (

) (
2

lim
x2

lim
x2

x+7

2x + 5 + x + 7

1
=K
2x + 5 + x + 7
1

2 ( 2) + 5 + 2 + 7

=K

2x + 5 x + 7
x2

2x + 5 + x + 7

2x + 5 x 7

x=2

lim f ( x ) = f ( 2 )

( x 2) (

x=2

f ( x ) is continuous at

x2

=K

=K

2x + 5 + x + 7
=K
2x + 5 + x + 7

( 2 x + 5) ( x + 7 )
=K
( x 2) ( 2x + 5 + x + 7 )
( x 2)
=K
( x 2) ( 2x + 5 + x + 7 )
1

lim 2 x + 5 + x + 7

=K

x 2

1
=K
9+ 9

1
=K
3+3
1
K=
6